2008
DOI: 10.1161/strokeaha.107.494823
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Smoking and Cardiovascular Disease in a Population With Low Cholesterol Levels

Abstract: Background and Purpose-The association of smoking with cardiovascular diseases in populations with low cholesterol levels is unclear and this lack of clarity may have contributed to the very high prevalence of smoking in East Asian men. The effect of smoking on stroke subtypes is particularly unclear. Methods-We used data from a prospective cohort study of 648 346 Korean men aged 30 to 64 years at their baseline assessment in 1992. Results-Mean (SD) total cholesterol at baseline was 4.9 (1.0) mmol/L and 59% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
3
23
2
1
Order By: Relevance
“…In a number of previous studies, including several from this population, 20,25,27 these risk factors have tended to have similar associations with IS and MI but different associations with IHS, lending support to the hypothesis that IS and MI share much of their etiology, but IHS differs in its etiology and pathophysiology. 31 Interestingly, in this study we found that the associations with FBG were stronger for IS than for MI, and indeed the association with MI was more similar to that for IHS.…”
Section: Sung Et Al Glucose Stroke and Myocardial Infarction 817supporting
confidence: 57%
“…In a number of previous studies, including several from this population, 20,25,27 these risk factors have tended to have similar associations with IS and MI but different associations with IHS, lending support to the hypothesis that IS and MI share much of their etiology, but IHS differs in its etiology and pathophysiology. 31 Interestingly, in this study we found that the associations with FBG were stronger for IS than for MI, and indeed the association with MI was more similar to that for IHS.…”
Section: Sung Et Al Glucose Stroke and Myocardial Infarction 817supporting
confidence: 57%
“…Multivariable-adjusted hazard ratios (HRs) and their 95% confidence intervals (CIs) for the development of stroke subtypes and myocardial infarction according to smoking status in Korean men aged 30 to 64 years enrolled in the Korean National Health System Prospective Cohort Study. 43 HRs were adjusted for age, height, blood pressure, body mass index, total cholesterol, hyperglycemia, alcohol consumption, regular exercise, income, and area of residence. Never smoking was used as the reference group.…”
Section: Hypercholesterolemiamentioning
confidence: 99%
“…In the Korean National Health System Prospective Cohort Study, 43 the association of smoking with the development of CVD was assessed using a large-scale cohort consisting of 648,346 Korean men with a 10-year follow-up. As shown in Figure 7, there were strong linear trends of increased risk of ischemic stroke, subarachnoid hemorrhage, and MI with greater number of cigarettes smoked per day.…”
Section: Smokingmentioning
confidence: 99%
“…A dose-response relationship exists between cigarette smoking and stroke risk. Smoking is a modifiable risk factor and cessation of smoking reduces the risk of stroke and other outcomes after several years of quitting [73]. In a cohort study of women, the stroke and cardiovascular mortality reached a comparable risk to never smokers after 20 years of cessation [74].…”
Section: Smokingmentioning
confidence: 99%